NEUROPSYCHOLOGICAL CHARACTERISTICS OF PEOPLE WITH DEVIANT BEHAVIOUR - Tkach, Bohdan (PSYCHOLOGICAL JOURNAL, 2018)
The article presents a casual structure of deviant behaviour, created on the basis of comprehensive and systematic neuropsychological study. It is suggested to conduct a neuropsychological study in conjunction with a biometric one (eye tracking and EEG) in order to reduce subjectivity in the interpretation of diagnostic tests results. Three components of symptom complex of deviances’ mental stage have been outlined by eliminating the alternatives. The initial symptom complex includes minor malfunctions of the frontal part of the brain: the orbitofrontal prefrontal cortex; the dorsolateral prefrontal cortex; anterior cingulate cortex; ventromedial prefrontal cortex. It has been established that the secondary symptom complex is predetermined by a personality being influenced by naïve realism, dominance of heuristic thinking and inability to apply expert thinking in everyday life; low communication competence; disadaptation resulting from inability to find in time the alternative ways of problem solving. The tertiary complex symptom is addiction itself – pathological homeostasis (constant desire to derive satisfaction), when addictive actions lose a conscious component and become an automated process. It appears that the choice of addictive behaviour pattern is not a stochastic process, but it depends on social background, a system of values and norms, financial situation and information environment. It has been found out that a normal functional state of the hippocampus predetermines hedonic motivation, and a weakened one – ataractic motivation. It has been established that all neuropsychological types of a personality with deviant behaviour are characterized by critical thinking reduction and automated performance of deviant actions. On the basis of continued EEG monitoring it was discovered that the people belonging to control groups are mostly left-brain dominant during the day and their brain activity is high enough, while the deviants are right-brain dominant during the day and when in anticipation and in the process of a deviant activity the left hemisphere is activated. The role of every neuropsychological profile of a personality in encouraging deviant tendencies or prevent them from spreading in the modern society has been defined.